​please answer it as fast as possible..

​Q3. What is the simplified form of the expression  m n x y   - n 2 y 2 - n m x y   +   m 2 x 2 + m 2 x 2   - n 2 y 2 n m x y  ?

         A.  - m x n y

         B.  m x n y  

         C.   m n x y

         D.  - x y m n
 

Dear student
We have,mnxy-n2y2-mnxy+m2x2+m2x2-n2y2mnxy=mnxymnxy-n2y2+m2x2-n2y2-mnxy+m2x2-mnxy+m2x2mnxy=mnxymnxy-n2y2+m2x2-n2y2-mnxy+m2x2-m2n2x2y2+m3nx3y=m2n2x2y2-mnxyn2y2-mnxym2x2+m4x4+n2y2mnxy-n2y2m2x2-m2n2x2y2+m3nx3y=-m3x3ny+mx-m2nx2yny+mx=mxny
Regards

  • 0
What are you looking for?